Research on corporate management accounting from the perspective of HeXie Management Theory - Lixia Wang; Chuan Zhang; Lijia Liu; Shiyan Wang; Xinyue Zhang (Cogent Business & Management)
This paper employs theoretical analysis and exploratory research methods to study the development and application of management accounting in terms of ‘people’ and ‘things’ and their coupling according to HeXie Management Theory. This findings indicate that enterprises should firstly set management accounting objective based on environment, organization and leadership (EOL). Subsequently, they should construct management accounting system and process of ‘things’ guided by Xie Principle, while also establishing an organizational framework of ‘people’ based on the He Principle. The next step involves coupling ‘people’ and ‘things’ in both time and space, followed by evaluating the performance of management accounting. The originality of the study are mainly (1) it adds the element of ‘people’ to the study of management accounting and extends the study to the perspective of integration of ‘people’ and ‘things’; (2)it also combines the HeXie Management Theory for the first time, and innovatively constructs a conceptual model of enterprise management accounting application, which provides a new theoretical basis for the field of management accounting.